Peran Moderasi Tingkat Senioritas Chief Financial Officer dalam Pengaruh Komposisi Wanita dan Ukuran Komite Audit Terhadap Manajemen Laba Riil - Michelle Tevi Goeinawan; Micheline Clarissa; Yulius Jogi Christiawan (Business Accounting Review, 2021)
Research on the effect of the composition of women and the size of the audit committee on real earnings management has been widely carried out with mixed results. Upper-echelon theory explains that the company's performance is influenced by the characteristics of its leaders such as the seniority level of the Chief Financial Officer (CFO). This study aims to examine whether the CFO seniority level can affect the relationship between audit committee characteristics and real earnings management. The study was conducted on 171 companies in three sectors listed on the IDX in 2018-2019. The data were analyzed by panel data regression using Gretl software. The results of data testing prove that the more female composition and the size of the audit committee can affect the real earnings management practice of a company. In addition, seniority level CFO is able to moderate the positive relationship between the composition of women in the committee on real earnings management. The results of the study are expected to be useful for shareholders to pay more attention to the composition of women and the size of the audit committee and the seniority level of CFOs to avoid real earnings management practices.